2019
DOI: 10.1039/c9cp04384e
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intentional photo-oxidation of a donor polymer and PC70BM on solar cell performance

Abstract: Bond breaking in the PC70BM cage and gap state formation explain inefficient charge collection upon photooxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…To investigate the sensitivity of fullerene acceptors to water vapor and oxygen, semiconductor films should be handled under inert conditions and the evolution of the electronic structure should be detected under dark conditions by controlling the volume of the water vapor or oxygen gas to exclude photochemical degradation. [ 133‐136 ] Bao et al . studied in situ oxygen and water vapor effects on fullerene acceptor [6,6]‐phenyl C61 butyric acid methyl ester (PC 61 BM).…”
Section: Environmental Effects On Energy Levels and Photovoltaic Prop...mentioning
confidence: 99%
“…To investigate the sensitivity of fullerene acceptors to water vapor and oxygen, semiconductor films should be handled under inert conditions and the evolution of the electronic structure should be detected under dark conditions by controlling the volume of the water vapor or oxygen gas to exclude photochemical degradation. [ 133‐136 ] Bao et al . studied in situ oxygen and water vapor effects on fullerene acceptor [6,6]‐phenyl C61 butyric acid methyl ester (PC 61 BM).…”
Section: Environmental Effects On Energy Levels and Photovoltaic Prop...mentioning
confidence: 99%
“…Investigations of the photodegradation mechanisms in such polymer-based solar cells have been focused on the light-absorbing component, the conjugated polymer, with the purpose of identifying and synthesizing more stable donor molecules [12][13][14] , while the photodegradation of the fullerene has been addressed in detail more recently [15][16][17][18][19][20][21] . We have previously shown that for the blend of the polymer TQ1 (poly[2,3-bis-(3-octyloxyphenyl)quinoxaline-5,8-diyl-altthiophene-2,5-diyl]) with PC 60 BM, the LUMO of PC 60 BM is much more affected by photooxidation than the LUMO of TQ1, contributing to the performance degradation 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21] We have previously shown that for the blend of the polymer TQ1 (poly[2,3bis-(3-octyloxyphenyl)quinoxaline-5,8-diyl-alt-thiophene-2,5-diyl]) with PC 60 BM, the LUMO of PC 60 BM is much more affected by photooxidation than the LUMO of TQ1, contributing to the performance degradation. 22,23 It is known that solid C 60 is air-sensitive and can quickly convert into a product with reduced solubility in apolar organic solvents, upon exposure to light at room temperature. 24 The triplet excited state of C 60 -based fullerenes readily transfers energy to an oxygen molecule, forming singlet molecular oxygen, 1 O 2 , or, alternatively, it transfers an electron to an oxygen molecule and forms a radical ion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that the equipment can be used to prepare thin films of polymer blends from solution in a safe and reliable way under microgravity conditions. We used a well-studied model system 1,14,[24][25][26] The results presented here show that the custom-designed equipment works as intended and that the dip-coated films can be produced under microgravity conditions. This also shows the possibility to transfer OSC production from Earth conditions to space conditions, a research field that presently is at an early stage with, to our knowledge, only two reports on exploring the use of OSCs in space applications.…”
mentioning
confidence: 99%